Analysis of School Principal Planning in Improving Teacher Competence at SMPN 5 Penukal Utara - Imani, Naila Putri; Ramdhani, Iqbal; Marlina, Leny; Karolina, Arsi (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The enhancement of teacher competence is essential to improving the quality of education. This study specifically examines the planning strategies implemented by the principal of SMPN 5 Penukal Utara to achieve this goal. Through a qualitative approach, the research explores the professional development programs undertaken, the principal's role in facilitating these activities, and teachers' perceptions of program effectiveness. The findings indicate that while the planning is generally well-structured, challenges remain in its implementation. These results underscore the importance of designing more effective teacher professional development programs in the future. This research aims to analyze the role of the principal's planning in improving teacher competence at SMPN 5 Penukal Utara. Teacher competence is a crucial factor in enhancing the quality of teaching and student learning outcomes. The study employs a descriptive qualitative method, collecting data through interviews, observations, and documentation. The findings reveal that the principal’s planning includes key aspects such as identifying teachers' training needs, developing continuous training programs, and conducting regular monitoring and evaluation. The principal plays a pivotal role in fostering pedagogical, professional, social, and personal competence among teachers through various activities, such as workshops, training sessions, and group discussions. The implementation of these plans has improved teachers' teaching skills and motivation. However, several challenges persist, including budget constraints and suboptimal teacher participation. Overall, effective planning by the principal can significantly enhance teacher competence, ultimately contributing to better educational outcomes at the school.